Optimizing Administrative Efficiency in Sewing Course Management : A Web-Based Application for Participant Registration and Attendance Monitoring at Bandung Vision Centre - Dani Rizky Zaelani; Budiman Budiman; R. Yadi Rakhman Alamsyah (International Journal of Information Engineering and Science, 2025)
The rapid growth of the fashion industry in Indonesia, particularly in Bandung, has increased the demand for structured and efficient sewing course management. Bandung Vision Center, as one of the institutions providing sewing training, faces significant administrative challenges due to the continued use of manual registration and attendance monitoring systems. These conventional processes result in data inaccuracies, slow information retrieval, limited transparency, and difficulties in monitoring participant progress across multiple training waves. This study aims to design and develop a web-based application to optimize participant registration and attendance monitoring processes at Bandung Vision Center. The research adopts an Agile software development methodology to ensure iterative development, flexibility, and responsiveness to user requirements. The system is implemented using the Laravel framework for backend development, ReactJS for frontend interface design, and MySQL as the relational database management system. System modelling is conducted using UML diagrams, and functionality testing is performed using the black-box testing method. The results indicate that the developed application significantly improves administrative efficiency, enhances data accuracy, and enables real-time monitoring of participant attendance. Additionally, the system increases transparency, facilitates structured data management, and supports better decision-making for course administrators. The implementation of this web-based application demonstrates its effectiveness in modernizing administrative processes and strengthening institutional competitiveness in the local fashion education sector. Future enhancements may include integration of online payment features, automated notifications, and advanced data analytics to further improve service quality and user satisfaction.